Another species of Quadrastichus (Hymenopera; Eulophidae; Tetrastichinae) attacking Erythrina (Fabaceae) in the Neotropics: a report from Costa Rica - Jansen-González, Sergio (2019)
Since the description of Quadrastichus erythrinae (Hymenoptera: Eulophidae: Tetrastichinae) in 2004, this invasive species has been reported in various tropical and subtropical regions, causing damage to several species of coral trees (Erythrina spp.). Here we report the presence of yet another invasive Quadrastichus attacking native and introduced species of Erythrina in Costa Rica. We present morphological evidence that strongly suggests that this species is not Q. erythrinae; rather, the species found in Costa Rica appears to be either Q. bardus or an undescribed species. We call for an urgent international effort to characterize the phytophagous Quadrastichus species associated with Erythrina species from around the world in order to clarify which species are invasive and document where these invasive species are currently known to occur. © 2019, African Association of Insect Scientists.